In vitro study: green synthesis and evaluation of MgO/C-dots/DOX phosphorescent nanocomposites for photodynamic/photocatalytic therapy of tumors - Karimi, M.; Sadeghi, E.; Zahedifar, M.; Nejati, M.; Mirzaei, H.; Hamblin, Michael R. (Frontiers in Bioengineering and Biotechnology, 2023)
MgO nanoparticles (NPs) and carbon dots (C-dots) were synthesized by co-precipitation and hydrothermal techniques. In the next step, as-synthesized NPs were modified by C-dots. Then, polyethylene glycol (PEG) was conjugated with MgO/Cdots. Finally, Doxorubicin (Dox) as an anticancer drug was loaded on MgO/Cdots/PEG nanocomposites. The XRD pattern showed the characteristic peaks of C-dots and MgO. The FTIR spectrum showed that MgO/C-dots possessed the carboxyl functional groups, allowing DOX to be loaded onto MgO/C-dots/PEG through hydrogen bonds. The particle size of MgO, C-dots, MgO/C-dots, and MgO/C-dots/PEG/DOX was 20-30, 5-10, 30-40, and 100-130 nm, respectively, using TEM, DLS, and FESEM techniques. MgO, MgO/C-dots, and MgO/C-dots/DOX were fluorescent NPs when excited by a UV source. Anthracene and methylene blue were used as fluorescent probes to identify the reactive oxygen species (ROS) produced by UV excitation. The activity of MgO/C-dots and MgO/C-dots/DOX against colorectal cancer (C26) cells, after repeated 5-min illumination with both UV-light and red light LEDs, were measured by MTT assay. C26 cancer cells incubated with DOX-loaded MgO/Cdots and exposed to either wavelength (UV and red) killed ~70% of cells. The green synthesized nanocomposites could act as anti-cancer photosensitizers probably by a photocatalytic mechanism.